Platelet Dense Bodies Loaded with Mepacrine Study in Chronic Idiopathic Thrombocytopenic Purpura (ITP) - Hourdille, P; Bernard, P; Reiffers, J; Broustet, A; Boisseau, M R (Thrombosis and Haemostasis, 1980)
In 22 cases of chronic ITP, the platelet 5-HT storage organelles were counted by examination of platelets loaded with mepacrine and correlated with the size and volume of the platelets. Statistical analysis showed that the mean volume and the number of granules increased in ITP without increase in the mean number of granules per unit volume. A strong correlation was found between platelet long diameter and number of dense bodies in controls (44 healthy subjects) (r = 0.94; y = 2.826 × – 0.699) and in ITP (r = 0.92; y = 2.587 × + 0.06). This study demonstrated in chronic ITP the presence both of platelets without granules and others rich in granules. These anomalies were present no matter what the count of platelets and did not change the mean values for granules and for ADP in most cases. Most platelets remain morphologically normal.
Keywords: I. T. P; Platelet dense bodies